Survival of Children Living With HIV on Art in Zambia: A 13-Years Retrospective Cohort Analysis - Munthali, Tendai; Michelo, Charles; Mee, Paul; Todd, Jim (Frontiers in Public Health, 2020)
Background: Research conducted before the introduction of anti-retroviral therapy (ART), showed that the majority of children living with HIV (CLHIV) would die before their second birthday. In Zambia, ART was rolled out to the public health system in 2004 with subsequent improved survival in CLHIV. However, the survival rates of CLHIV on ART in Zambia since 2004 have not been extensively documented. We assessed survival experiences and the factors associated with survival in CLHIV on ART in Zambia. Methods: We conducted a retrospective cohort analysis of CLHIV (aged up to 15 years) using routinely collected data from health facilities across Zambia, over 13 years to ascertain mortality rates. We explored survival factors using Cox regression giving adjusted hazard ratios (AHR) and 95% confidence intervals (95% CI). Nelson Aalen estimates were used to show the cumulative hazards of mortality for different levels of explanatory factors. Results: A total of 65,448 eligible children, were initiated on ART between 2005 and 2018, of which 33,483 (51%) where female. They contributed a total survival time of 275,715-person years at risk during which 3,265 children died which translated into an incidence rate of 1.1 deaths per 100 person-years during the review period. Mortality rates were highest in children in the first year of life (Mortality rate 2.24; 95% CI = 2.08–2.42) and during the first year on ART (Mortality rate 3.82 95% CI = 3.67–3.98). Over 50% of the children had been on ART for 5–10 years by 2018, and they had the lowest risk of mortality compared to children who had been on ART for <5 years. Conclusions: Children with HIV in Zambia are surviving much longer than was predicted before ART was introduced 14 years ago. This key finding adds to the literature on analysis of survival in CLHIV in low income settings like Zambia. However, this survival is dependent on the age at which ART is initiated and the time on ART highlighting the need to increase investments in early infant diagnosis (EID) to ensure timely HIV testing and ART initiation for CLHIV.